A carrier leakage calibration and compensation technique for wideband wireless transceiver - 周立国 彭锦 袁芳 方治 颜峻 石寅 (Journal of semiconductors, 2014)
A carrier leakage calibration and compensation technique based on digital baseband for a wideband wireless communication transceiver is proposed. The digital baseband transmits a calibration signal, samples the signal which passes through the transmitter path and the calibration loop in the RF chip, measures the carrier leakage by analyzing the sampled data and compensates it. Compared with a self-calibration technique in the RF chip, the proposed technique saves area and power consumption for the wireless local area network （WLAN） solution. This technique has been successfully used for 802.1 In system and satisfies the requirement of the standard by achieving over 50 dB carrier leakage suppression.